2020
DOI: 10.1039/c9tc06544j
|View full text |Cite
|
Sign up to set email alerts
|

Engineering polymers with improved charge transport properties from bithiophene-containing polyamides

Abstract: Incorporation of bithiophene segments in the polyamides results in semiconducting properties, while mechanical properties of typical engineering polyamides are maintained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 50 publications
(60 reference statements)
0
5
0
Order By: Relevance
“…Nevertheless, our results demonstrate that hydrogen bonding is not only compatible with charge transport in p‐type organic semiconductors, but reinforces the structural elements required for good π overlap. Hence, the use of hydrogen‐bonded side groups will provide a general pathway for novel organic semiconductors, such as semiconducting polyamides, with improved morphology and device performance …”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, our results demonstrate that hydrogen bonding is not only compatible with charge transport in p‐type organic semiconductors, but reinforces the structural elements required for good π overlap. Hence, the use of hydrogen‐bonded side groups will provide a general pathway for novel organic semiconductors, such as semiconducting polyamides, with improved morphology and device performance …”
Section: Resultsmentioning
confidence: 99%
“…42,43 We recently reported semicrystalline semiaromatic polyamides with bithiophene units and demonstrated that such materials indeed combined the thermomechanical characteristics of typical semiaromatic engineering polyamides with significant charge carrier mobility. 44 Here, we report the first example of polyamides containing electron deficient, n-type semiconducting dicyanoperylene bisimide repeat units. Four such polyamides with different aliphatic spacer lengths were found to show not only good thermal stability and shear moduli in the range 0.75-0.93 GPa, but also H-type coupling of the dicyanoperylene bisimide chromophores in the solid-state, and charge carrier mobilities of about 0.01 cm 2 V -1 s -1 .…”
Section: Introductionmentioning
confidence: 90%
“…[56][57][58] Moreover, in common with other polyamides derived from centrosymmetric aromatic diacids and linear aliphatic diamines with even n, PAnPBICN2 (n = 6, 8, 10, 12) is expected to show a stable a-type crystalline phase in which fully extended aliphatic linkages form stacked planar hydrogen-bonded sheets. 10,44 At the same time, in order to maintain a reasonable packing density, the chain direction of the aliphatic linkages must be strongly tilted away from the planes of the more bulky perylene moieties.…”
Section: Crystalline Morphology Of the Polyamidesmentioning
confidence: 99%
“…Hydrogen‐bonded side chains have also proven to be of interest for polymer semiconductors, [51, 52] whose solid‐state morphology can be modified by incorporating amide functions, resulting in improved performance in both field‐effect transistors and photovoltaic devices compared with their non‐hydrogen‐bonded counterparts. Similarly, the introduction of π‐conjugated segments into polyamides has recently been reported to provide materials that combine promising optoelectronic properties with mechanical properties comparable to those of structural polyamides [53, 54] . Moreover, the use of hydrogen‐bonded acetamide end groups has been shown to induce tighter packing of quaterthiophene derivatives than in related quaterthiophene acetates, resulting in more efficient π‐overlap and a stronger tendency to form well‐ordered lamellar structures, and excellent performance in organic field‐effect transistors [55] .…”
Section: Introductionmentioning
confidence: 99%
“…Similarly,the introduction of p-conjugated segments into polyamides has recently been reported to provide materials that combine promising optoelectronic properties with mechanical properties comparable to those of structural polyamides. [53,54] Moreover, the use of hydrogen-bonded acetamide end groups has been shown to inducet ighter packing of quaterthiophene derivatives than in relatedq uaterthiophene acetates,r esulting in more efficient p-overlap and as tronger tendency to form wellordered lamellar structures, and excellent performance in or-ganic field-effect transistors. [55] However,s ystematic investigations of this type of hydrogen-bonded organic semiconductor have rarely been reported for crystalline materials from lowmolecular-weight p-conjugated compounds.…”
Section: Introductionmentioning
confidence: 99%